Adverse event assessment and reporting in trials of newer treatments for post‐operative pain. Issue 7 (16th March 2016) - Hoffer, D.; Smith, S. M.; Parlow, J.; Allard, R.; Gilron, I.
Abstract : Background: Assessment and reporting of adverse events (AEs) in studies of perioperative interventions is critical given the potential for unintended and preventable iatrogenic morbidity and mortality. This focused review evaluated the quality of AE assessment and reporting in acute post‐operative pain treatment trials. Since older analgesics (e.g., opioids, NSAIDs) already have a well‐characterized safety profile, we concentrated on trials of pregabalin and gabapentin as a representative sample of studies where the perioperative safety profile was relatively unknown. Methods: We reviewed primary reports of trials of pregabalin and gabapentin for treatment of acute post‐operative pain for: (1) adherence to the 10 recommendations from the 'CONSORT Extension for Harms, ' (2) AE assessment method, (3) timing of AE assessment and reporting, and (4) assessment and reporting of AE severity. Results: We identified 31 trials of pregabalin and 59 of gabapentin. The median number of CONSORT harms recommendations that were satisfied was 7 of 10. The most common (41%) method of AE assessment was direct questioning about specific AEs by investigators. However, AE assessment method was not described in 18% of trials. AE assessments were reported for specified perioperative time points in only 24% of trials. Of greatest concern, no AE data were reported whatsoever in 8 of the included publications. Conclusions: Considerable widespread improvements are needed in AE reporting for post‐operative pain treatment trials. In addition to heightened awareness among clinical investigators, mandatory journal editorial policies may further facilitate improvements in safety assessment and reporting.